2020
DOI: 10.1155/2020/8869810
|View full text |Cite
|
Sign up to set email alerts
|

Structural Damage Identification Based on the Wavelet Transform and Improved Particle Swarm Optimization Algorithm

Abstract: A method based on the wavelet transform and improved particle swarm optimization (WIPSO) algorithm is proposed to identify the microdamage of structures. First, the singularity of wavelet coefficients is used to identify the structural damage location, and then, the improved particle swarm optimization (IPSO) algorithm is used to calculate the optimal solution of the objective function of the structural damage location to determine the structural damage severity. To study the performance of WIPSO, the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…To measure strain, the curvature mode can be used for indirect measurement. According to the material mechanics, the bending static relation of the beam can be obtained as [ 15 ] where i is the section position of measuring point i , M i is the bending moment of section i , E i I i is the flexural rigidity of section i , d i is the radius of curvature at section i , and ρ i is the curvature of section i . According to the approximate equation of bending deformation of the beam [ 15 ], where x is the coordinate along the length direction of the straight beam and y is the bending deflection of the beam.…”
Section: Wavelet Based Data Coupling Methods (W-dcm)mentioning
confidence: 99%
See 2 more Smart Citations
“…To measure strain, the curvature mode can be used for indirect measurement. According to the material mechanics, the bending static relation of the beam can be obtained as [ 15 ] where i is the section position of measuring point i , M i is the bending moment of section i , E i I i is the flexural rigidity of section i , d i is the radius of curvature at section i , and ρ i is the curvature of section i . According to the approximate equation of bending deformation of the beam [ 15 ], where x is the coordinate along the length direction of the straight beam and y is the bending deflection of the beam.…”
Section: Wavelet Based Data Coupling Methods (W-dcm)mentioning
confidence: 99%
“…According to the material mechanics, the bending static relation of the beam can be obtained as [ 15 ] where i is the section position of measuring point i , M i is the bending moment of section i , E i I i is the flexural rigidity of section i , d i is the radius of curvature at section i , and ρ i is the curvature of section i . According to the approximate equation of bending deformation of the beam [ 15 ], where x is the coordinate along the length direction of the straight beam and y is the bending deflection of the beam. According to Eqs ( 1 ) and ( 2 ), the difference equation of three equidistant continuous measuring points along the beam can be obtained [ 16 ]: where i +1, i , and i −1 are three adjacent continuous mea-suring points with equal distance along the beam, ρ i is the curvature of section i , y i is the bending deflection of section i , y i +1 and y i −1 are the bending deflections of section i −1 and section i +1 of the measuring points, respectively, and Δ is the distance of two adjacent measuring points.…”
Section: Wavelet Based Data Coupling Methods (W-dcm)mentioning
confidence: 99%
See 1 more Smart Citation
“…e combination of wavelet analysis and IA can effectively synthesize the advantages of both so as to maximize the efficiency of structural damage identification. Compared with other IAs, PSO and GA are widely applied in structural damage identification [32][33][34][35][36][37]. In this study, the microdamage severity is defined to be within 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [ 27 ] constructed a crack identification index based on WT to locate the opening crack position of Functionally Graded Materials (FGMs). Furthermore, Guo et al [ 28 ] reported that the detail coefficients of WT were highly sensitive to damage. They applied these coefficients to successfully detect the location and severity of structural damage.…”
Section: Introductionmentioning
confidence: 99%